Analysis and optimization of the reactive power compensation modes in a power supply system - Yagup, Valeriy; Yagup, Katerina; Kovalova, Yuliia; Kharchenko, Viktor; Besarab, Tetiana; Krasnov, Oleksii; Domanskii, Illya; Domanskii, Vasilii; Kostin, Hennadii; AbuGoukh, Haidar Gafar (Eastern-European Journal of Enterprise Technologies, 2019)
The paper reports the study of modes in a single-phase generalized power supply system in terms of improving energy indicators in the system by compensating for the reactive power. We considered three test versions of the power supply system with different ratios of complex load impedance and power lines. We show the drawbacks of the traditional method for calculating the parameters of the compensating device, which provide partial compensation of reactive power consumed only by the load. An analysis of the partial compensation mode indicates that with an increase in the reactivity of the transmission line, the energy indices, which can be obtained as a result of reactive power compensation, deteriorate. Using search engine optimization, it is shown that an increase in the capacity of the compensator is required for full compensation. The method of search engine optimization is implemented in the Mathcad software package using the given-find decision unit. For this purpose, we used the equations of the mathematical model of the power supply system based on component and topological equations. As additional conditions, we used relations that determine the reactive power of the supply source full compensation, as well as the conditions for the physical implementation of the compensating device structure. The optimization variables are the parameters of the mode under study and the parameters of the compensating device. Fragments of texts in the program with numerical solutions are presented, as well as comparative tables of analysis and optimization results of reactive power compensation modes in the studied power supply systems for all variants of their parameters. The quantitative estimates of additional capacity value are given, which is calculated based on the condition for the compensation of reactive power in the transmission line by it. Our study has shown that with an increase in the reactance of the transmission line, full compensation cannot be achieved with the use of shunt compensation and physical interpretation of this phenomenon. It implies that the voltage on the compensating shunt capacitor decreases faster than the reactive power of the transmission line compensated by it increases. It is shown that in the latter case, the full compensation of reactive power can still be achieved by using combined series-shunt compensation.